Bearing witness : Native American voices in Hollywood [videorecording (DVD)] - Cardinal, Tantoo; Bedard, Irene, 1967- (Deskpop Entertainment, 2025)
For over a century, Hollywood cinema has crafted the "villainous Indian" in its Westerns, a genre embodying American racism to obscure the genocide upon which the U.S. was built. For decades, Westerns glorified "Manifest Destiny," celebrating the conquest of so-called "wild" lands, regardless of who stood in the way. It wasn't until the Vietnam War, the civil rights movement, and 1960s-70s protests that a shift occurred. Films like Little Big Man and Soldier Blue finally humanized Native Americans, depicting the massacres they undured and offering a more truthful portrayal of history.